IMPLEMENTATION OF SELF-AWARENESS IN PROJECT MANAGER EMOTIONAL INTELLIGENCE - Iftita, Rosela; Arisandy, Desy (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
PT Digital Desa Indonesia has a vision to maximize the potential of Indonesian villages through digital products, so it's critical for the businesses to manufacture high-quality goods and support the development of villages. Therefore, the fundamental indicator of a project's success in product development is a professional project manager. Through the incorporation of self-awareness into the project work processes, this service seeks to increase the emotional intelligence of project managers. Application of this program refers to the three phases of the project workflow, namely planning, implementation, and monitoring, and the job description for the position of Project Manager. Project managers have high emotional intelligence as a competency in human resource firm development as a result of applying self-awareness at program. Data were gathered through unstructured interviews and observations. Emotional intelligence is a requirement for project manager jobs to perform their duties and obligations. Self-awareness in particular needs to be grasped as a fundamental component.